Sebaceous Carcinoma of the Vulva: A Case Report and Review of the Literature - Hind Alharthi (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
Sebaceous carcinoma is a rare malignant cutaneous neoplasm that is most commonly arises in the ocular region. Although it can occur in extraocular sites, sebaceous carcinoma is rarely encountered in the vulva. The use of immunohistochemical staining is very crucial to exclude other differential diagnoses including primary cutaneous and metastatic neoplasms. Unlike ocular sebaceous carcinoma, little is known about the clinical behavior and the prognostic factors in vulvar sebaceous carcinoma. Herein, we present a case of vulvar sebaceous carcinoma in a 27-year-old female, who presented with a labial tumor with lung metastases. To the best of our knowledge, only 11 similar cases were previously reported in the literature.